Penerapan Kebijakan Larangan Mudik Lebaran pada Masa Pandemi Covid-19 dalam Perspektif Masyarakat Indonesia - Tsaabita, Aldila Nisa Ilmatu (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2021)
Homecoming is one of the unique cultures where Indonesian people go to their hometowns during Eid. Sometimes going home is the main cause of traffic jam and crowds in some areas. This is a big challenge for the Indonesian people in the midlle of the Covid-19 pandemic. The government issued a ban on going home in 2021 aimed at reducing the spread of Covid-19 in Indonesia. The issuance of the policy caused various perceptions from the public. Community responses and perspectives are very important aspects in analyzing policy success. So that a study was conducted on how the public's perception of the ban on going home during the COVID-19 pandemic era was conducted. The research was carried out thoroughly covering the entire territory of Indonesia and carried out online. This research method uses a descriptive quantitative approach to Secondary Data Analysis (SDA). The results of this study are data on the decrease in the volume of homecomers, in 2020 the number of homecomers is 10.44% while in 2021 it is 4.6%. This proves that the community's perspective after the issuance of the homecoming ban policy is getting better and shows the results that the community provides a positive perspective. The government creates a positive perspective for the community regarding the ban on going home through the use of social media and technology, organizing a video contest for Eid gathering, and a sociological anthropological approach. Keywords: Covid-19;Government;Homecoming; Perception